Strategies for the Implementation of Islamic Values in Democracy to Realize Social Harmony - Tatik Sri Wulandari; Miftahul Huda; Masdar Hilmy (STAI Terpadu Yogyakarta, 2025)
This research aims to identify effective strategies in implementing Islamic values in the democratic system to realize social harmony, as well as identify challenges and opportunities in its implementation. The method used is a qualitative approach with phenomenology. The results of the study show that the implementation of Islamic values in democracy requires the integration of principles such as justice, freedom, and responsibility with a deliberation-based democratic process. Effective strategies include political education based on Islamic values, the application of shura principles (deliberation) in policy, and the strengthening of democratic institutions. The main challenges faced include differences in the interpretation of Islamic teachings, conflicts between religious values and practical politics, and a lack of integration of Islamic moral education with democratic principles. In the villages of Karangpatihan, Blembem, and Bringinan, differences of opinion on Islamic teachings hinder people's understanding of freedom and justice in democracy, which requires inclusive dialogue to reach an agreement. The implication of this research is the need for cooperation between the community, government, and religious institutions to ensure successful implementation and the importance of integrating Islamic moral education in the education system to create a just and harmonious society.